Potential and economics of ashwagandha (Withania somnifera (Linn.) Duna!) in overlapping cropping system under rainfed conditions of sub-tropical North India - Singh, Man Singh, U B Singh, Saudan Singh, S P S Khanuja, Aparbal (Journal of Spices and Aromatic Crops, 2003)
Field experiments were conducted at Central Institute of Medicinal and Aromatic Plants, Lucknow to find out production potential and economic returns of traditional monocropping systems vis-a-vis alternative cropping system. The cropping systems evaluated were: pearl millet (Pennisetum glaucum) fallow, maize (Zea mays) - fallow and okra (Ablmoschus esculentus) - fallow (traditional monocropping system) and medicinal plant, ashwagandha (Withania soml1iftra), at low (100 x 103 plants ha-1) and high (200 x 103 plants ha-1) population densities (LPD and BPD, respectively), as mono as well as overlap crop "’ith pearl millet, maize or okra (alternate cropping systems). All the overlapping cropping systems recorded higher productivity in tenns of pearl millet grain equivalent yield (PGEY) and economic returns over traditional cropping systerns. Pearl mlilet-ashwagandha (at HPD) overlapping cropping system; recorded 6.8 to 176.7% higher PGRY over remaining traditional as well as alternate cropping systems; the minimum being over maize-aswagandha and maximum over maize-fallow. The corresponding increase in net economic returns was 22.4-278.7%. Ashwagandha at HPD of 200 x 103 plant ha-1 under monocropping yielded 53.8% and 66.7-73.3% higher roots than it was grown at LOP under monocropping and overlapping cropping systems, respectively. Also, ashwagandha at either of the population densities under monocropping system proved more economical than traditional mono cropping systems. Better yield and economic returns make ashwagandha an ideal crop for moisture stress rainfed conditions. Overlapping cropping of ashwagandha is suggested as a way to improve the productivity and economic returns from resource constrained rainfed agriculture in sub-tropical North India.